Determinants of Financial Inclusion in Egypt - Sayed, Mohamed Noureldin; Shusha, Amir (Asian Economic and Financial Review, 2019)
The purpose of the study is to evaluate the determinants of financial inclusion in Egypt. Specifically, the present study seeks to determine whether access to financial services, usage of financial service, and knowledge levels of the financial services have determined financial inclusion in Egypt. The descriptive research design has been adopted while targeting 470 managers in commercial banks operating in Egypt. All questionnaires have been returned fully answered and fit for analysis. Going by the descriptive and inferential statistics on the use of financial services, it is evident that a large number of consumers in Egypt have integrated different financial products and services in their consumption process. In respect to this, the availability of different financial services and products influences the consumption of financial services. The research study further underlines the centrality of religion in influencing consumption of financial services in Egypt. Concerning this point, it is imperative for financial institutions to consider integrating religious principles in designing financial products and services in increasing consumption of financial services amongst consumers. There is also a significant effect of knowledge levels of financial services and consumption. The findings of this study reveal that despite the high rate of uptake of different financial services and products, it is imperative for financial institutions in Egypt to consider diversifying their financial products and services. The study recommends that financial firms should develop diversified financial products in order to align with the customers’ needs. Amongst the financial products and services that should be developed relate to banking and insurance products.